Culture Moderates the Normative and Distinctive Impact of Parents and Similarity on Young Adults' Partner Preferences. (December 2020) - Locke, Kenneth D.; Barni, Daniela; Morio, Hiroaki; MacDonald, Geoff; Mastor, Khairul A.; de Jesús Vargas-Flores, José; Ibáñez-Reyes, Joselina; Reyes, Jose Alberto S.; Kamble, Shanmukh; Ortiz, Fernando A.
To examine cultural, parental, and personal sources of young adults' long-term romantic partner preferences, we had undergraduates ( n = 2, 071) and their parents ( n = 1, 851) in eight countries (Canada, India, Italy, Japan, Mexico, Malaysia, Philippines, the United States) rate or rank qualities they would want in the student's partner. We introduce and use a method for separating preference patterns into normative patterns (shared across families and generations) and distinctive patterns (that characterized particular families or individuals). We found that youth everywhere wanted partners who aligned with both their own dispositions and their parents' preferences, and these alignments reflected both culturally normative preferences and preferences distinctive to specific individuals or families. Students also predicted their parents' responses: Their predictions were reasonably accurate reflections of what a typical parent prefers, but also reflected distinctive assumed agreement (i.e., they overestimated the degree to which their particular parents shared their particular preferences for qualities that diverged from culturally normative ideals). Culturally normative patterns exerted a stronger influence on actual or assumed parent–child agreement and accuracy in relatively collectivistic Southeast Asia (Philippines and Malaysia) than in relatively individualistic English-speaking North America (the United States and Canada). Conversely, preferences for partners who shared one's distinctive personal dispositions were stronger in Western than Asian countries.